Ozonotherapy for inflamatory diseases in female genital organs (Ozone Therapy Global Journal, 2011)
For treatment of 100 patients with non-specific colpitis a method of streaming Ozonetherapywas used with assistance of the ozone generator MEDOZONS-BM and specialattachment on the basis of vaginal speculum. The irrigation with an ozone-oxygen mixturewith ozone concentr ation of 2000 mcg/L was carried out within 5 minutes afterpreliminary moistening of mucosa with sterile bi-distilled water. In the course of the investigationsit was established that along with a positive clinical effect, ozonetherapycaused an impr ovement in vag i nal local immunit y ind i ces – a credible increase inlysozyme in 70% of patients, a decrease in IgG level in 60% of patients, stabilizationof cervical mucus myeloperoxidase in 80% of patients.Also we have used intrauterine irrigations with ozonized bi-distilled water in case ofacute endometritis. This method of treatment has been provided to 100 patients withpostnatal and postabortive endometritis. Based on the received results, we have drawna conclusion that in the course of treatment all patients showed an improvement ingeneral state, body temperature returned to normal, symptoms of intoxication decreased,sleep and appetite got better, pain syndrome disappeared faster and pathologicaldischarges were eliminated. The results of laboratory investigations have demonstrateda credible decrease in ESR, normalization of leukocyte numbers and an decreasein circulating immune complexes.Thus, for treatment of non-specific colpitis and endometritis we may recommend thegiven method of ozonetherapy to be used in combination with a basic anti-inflammatorytherapy.